INOVASI PEMBUATAN ABON CUMI UNTUK PENGEMBANGAN PRODUK KREATIF DAN UMKM DI DESA KERUAK - Parawansyah, Khofifah Indah Parawansyah; Putri, Zarina Putri; Azkia; Elsa; Ida Wayan Bagus; Jania Haerun; M. Abil; Sidqi Atma Nadi; Zohratul; Zulkifli; Baiq Nilawati; Parawansyah, Khofifah Indah; Putri, Zarina; Zakira, Azkia; Apriliani, Elsa; Kresna, Ida Wayan Bagus; Nisa, Jania Haerun; Basri, M. Abil; T, Sidqi Atma Nadi; Isnaini, Zohratul; Zulkifli, Zulkifli; Astini, Baiq Nilawati (Universitas Mataram, 2024)
The development of squid floss products as an innovation in the micro, small, and medium enterprise (MSME) sector in Keruak Village, East Lombok Regency, is a strategic effort to enhance the added value and competitiveness of local fishery products. Keruak Village holds significant potential in the fisheries industry; however, limitations in processing technology and marketing have constrained this sector's contribution to the local economy. This study aims to examine the innovation process of squid floss products, identify the challenges faced by MSME actors, and evaluate the economic and social impacts of this innovation on the local community. However, challenges such as limited access to technology and markets still need to be addressed to ensure the sustainability of this innovation.